Characterisation of clinically important Staphylococcus and Enterococcus species prevalent in livestock, human contacts and water samples in Gauteng, South Africa - Ehlers, M.M. (Marthie Magdaleen) (2026)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2014.